A new species of treefrog (Litoria: Pelodryadidae) from the karstic South-fold Mountains of New Guinea - Oliver, Paul M.; Mcdonald, Peter J.; Dahl, George; Nagombi, Elizah; Richards, Stephen J. (Zootaxa, 2024)
The frog fauna of New Guinea is exceptionally diverse but very poorly known. Here we describe a new species of pelodryadid treefrog that is currently known only from two specimens from a single site in Hela Province in the highlands of Papua New Guinea. Genetic data show that the new species is closely related to the torrent-breeding species Litoria angiana (Boulenger, 1915) from which it can be readily distinguished by its more slender body and limbs, relatively long forelimbs, and aspects of body colouration and tuberculation. The type locality is on Gigira Ridge, a massive limestone spur extending off New Guinea’s Central Cordillera and we hypothesise that the distinctive slender limbs and relatively long forelimbs of the species may be adaptations for clambering, either in complex montane forest habitats or potentially within karst. The ongoing discovery of rare and seemingly localised frog species in Melanesia emphasises that recent estimates of a regional anuran fauna in excess of 700 species that were derived from known candidate species are likely conservative.